Differential Impact of Plant Secondary Metabolites on the Soil Microbiota - Schütz, Vadim; Frindte, Katharina; Cui, Jiaxin; Zhang, Pengfan; Hacquard, Stéphane; Schulze-Lefert, Paul; Knief, Claudia; Schulz, Margot; Dörmann, Peter (Frontiers in Microbiology, 2021)
Plant metabolites can shape the microbial community composition in the soil. Two indole metabolites, benzoxazolinone (BOA) and gramine, produced by different Gramineae species, and quercetin, a flavonoid synthesized by many dicot species, were studied for their impacts on the community structure of field soil bacteria. The three plant metabolites were directly added to agricultural soil over a period of 28 days. Alterations in bacterial composition were monitored by next generation sequencing of 16S rRNA gene PCR products and phospholipid fatty acid analysis. Treatment of the soil with the plant metabolites altered the community composition form phylum to ASV level. Alpha diversity was significantly reduced by BOA or quercetin, but not by gramine. BOA treatment caused a decrease of the relative abundance of 11 ASVs, while only 10 ASVs were increased. Gramine or quercetin treatment resulted in the increase in relative abundance of many more ASVs (33 or 38, respectively), most of them belonging to the Proteobacteria. Isolation and characterization of cultivable bacteria indicated an enrichment in Pseudarthrobacter or Pseudomonas strains under BOA/quercetin or BOA/gramine treatments, respectively. Therefore, the effects of the treatments on soil bacteria were characteristic for each metabolite, with BOA exerting a predominantly inhibitory effect, with only few genera being able to proliferate, while gramine and quercetin caused the proliferation of many potentially beneficial strains. As a consequence, benzoxazolinone or gramine biosynthesis, which have evolved in different barley species, is accompanied with the association of distinct bacterial communities in the soil, presumably after mutual adaptation during evolution.